Reversal of Autoimmune Diseases Through Dietary Modifications - Naqvi, Rehan; Mehdi, Asghar; Anjum Zehra; Das, Geetha Kumari; Ahmed, Zameer; Zameer, Sambreen (MultiTech Publisher, 2024)
Autoimmune ailments are chronic environments resulting from the invulnerable system's dysfunction, chiefly the frame ambushing its tissues. While usual situations devote effort to symptom administration and invulnerable abolition, emerging research desires that digestive modifications can play a crucial role in overturning autoimmune ailments. This paper presents a case study of an individual who favorably developed their autoimmune disease through distinguishing digestive changes.The member, diagnosed with accompanying [distinguishing autoimmune ailment], implemented abstinence from food modifications over a [particularized period of time]. Data collection arrangements contained interviews, digestive records, and health appraisals. The results show meaningful improvements in [list specific manifestations or gravestones] situated in [relevant dossiers] in the way that testing room results or symptom appraisals These improvements were assigned to the dietary changes that contained [describe the digestive changes]. The argument surveys the mechanisms behind these improvements, seeing determinants such as the gut microbiome, redness, and invulnerable whole regulation. The study's restraints, including the lack of a control group and potential biases, are also discussed. This record of what happened climaxes the potential of dietary invasions as a comprehensive approach to common treatments in the administration and about-face of autoimmune afflictions. While further research is needed for more extensive inference, this case provides valuable insights into the impact of embodied food procedures on autoimmune disease administration